PENGARUH MATA KULIAH KEWIRAUSAHAAN TERHADAP SIKAP, MOTIVASI DAN MINAT BERWIRAUSAHA MAHASISWA AKUNTANSI UNIVERSITAS PRIMA INDONESIA - Tina Novianti Sitanggang; Faathir Nurul Yaasiin (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This research was conducted at Prima Indonesia University. The purpose of this study was to analyze the effect of entrepreneurship courses on attitudes, motivation and interests of accounting students at Prima Indonesia University in entrepreneurship. The sample in this study was 236 respondents who were taken using the Slovin formula. The data were processed using SPSS assistance. The analytical tool used in this study is multiple linear regression. The results of this study indicate that the variables of entrepreneurial knowledge, attitudes and motivation have a significant effect on entrepreneurial interest